Long-acting stain-resistant crack-resistant high-strength UHPC decorative component and preparation method thereof

By adopting a double-layer combination structure of structural layer and surface layer in UHPC decorative components and adding specific components, the shortcomings of existing UHPC decorative components in terms of stain resistance, crack resistance and durability are solved, and long-term efficiency is achieved It is stain resistance, crack resistance and high durability, reducing costs and environmental pollution.

CN119430788APending Publication Date: 2025-02-14CHINA STATE CONSTRUCTION ACADEMY CORPERATION LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411340523.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing ultra-high performance concrete (UHPC) decorative components have shortcomings in terms of stain resistance, crack resistance and durability, and often require spraying of masking agent to improve protection, but this increases costs and environmental pollution.

Method used

Using a double-layer combination structure of structural layer and surface layer, the structural layer contains fibers to improve mechanical properties. The surface layer achieves hydrophobic self-cleaning and photocatalytic degradation by adding components such as aqueous stearic acid emulsion, nano-TiO2 and modified zeolites. Clean and crack resistance.

Benefits of technology

It realizes long-term stain resistance, crack resistance and high durability of UHPC decorative components, reduces dependence on masking agents, reduces costs and environmental pollution, and improves the decoration effect and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059548490000061
    Figure BDA0005059548490000061
  • Figure BDA0005059548490000071
    Figure BDA0005059548490000071
  • Figure BDA0005059548490000081
    Figure BDA0005059548490000081
Patent Text Reader

Abstract

The invention belongs to the technical field of ultra-high performance concrete decoration, and particularly relates to a long-acting stain-resistant crack-resistant high-strength UHPC decoration component and a preparation method thereof. The UHPC decorative component comprises a structural layer and a surface layer, the structural layer is prepared from the following raw materials: white cement, a white mineral admixture, white quartz powder, fibers, white quartz sand, a water reducing agent, a defoaming agent and water; the surface layer is prepared from the following raw materials: white cement, a white mineral admixture, white quartz powder, white quartz sand, a water reducing agent, a defoaming agent, water, a water-based stearic acid emulsion, zeolite and nano TiO2. The UHPC decorative component not only has good mechanical properties and long-acting stain resistance, but also omits the procedure of spraying a finishing agent on the UHPC decorative component, and can save the construction period and reduce environmental pollution while saving the cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ultra-high performance concrete decoration, and specifically relates to a long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component and a preparation method thereof. Background Art

[0002] Ultra-High Performance Concrete (UHPC) is a new type of cement-based material with ultra-high mechanical properties and durability. It is widely used in lightweight, high-rise, large-span, and highly durable engineering structures. In recent years, with the introduction of the concept of green building, its excellent decorative performance has gradually become a research hotspot. Using it as a decorative material can solve the defects of ordinary decorative concrete such as low tensile strength, poor toughness, heavy weight, and easy cracking, which is conducive to expanding its application range and realizing structural decoration integration. In the past ten years, UHPC has helped architects around the world realize many elegant architectural shapes. In terms of improving the decorative effect of UHPC decorative components, the current method is mainly to apply a layer of topcoat protective agent on the surface.

[0003] Chinese patent CN117844370A discloses an organosilicon waterproofing agent for ultra-high performance concrete panels and a preparation method thereof: comprising 5-20 parts of hydroxy silicone oil, 2-10 parts of silane coupling agent, 1-5 parts of amino silicone oil, 1-10 parts of nano-white carbon black and 50-100 parts of organic solvent. The organosilicon waterproofing agent obtained in this patent has a certain degree of hydrophobicity, but only has a layer of protection on the surface of concrete, and this layer of protection has low strength and is prone to aging and failure. Once the protective layer is damaged, the protective effect will disappear, and the durability is poor and the effect cannot be maintained for a long time.

[0004] Chinese patent CN117430386A discloses a self-luminous, self-cleaning, highly crack-resistant UHPC curtain wall panel surface protection material and preparation method: 30% to 40% cement, 5% to 7.5% glass powder, 17% to 23% glass sand, 20% to 25% luminescent material, 0.6% to 0.9% nano-TiO2, 8% to 12% high molecular polymer emulsion, 0.5% to 0.8% water reducer, 0.2% to 0.4% shrinkage reducer and 2.5% to 5% water, the sum of the mass percentages of each component is 100%. The surface protection material obtained by this patent has low strength and a large gap in durability compared with UHPC. With the increase of service time, it will age and fall off under the influence of factors such as temperature, stress, and light, and eventually lose its protective effect.

[0005] From the above, it can be seen that the development of UHPC decorative components with high strength, high durability and excellent anti-fouling performance has very important practical significance. Summary of the invention

[0006] The purpose of the present invention is to provide a long-term stain-resistant and crack-resistant high-strength UHPC decorative component and a preparation method thereof. The UHPC decorative component not only has good mechanical properties and long-term stain resistance, but also eliminates the process of spraying a finishing agent on the UHPC decorative component, thereby saving costs, shortening construction time, and reducing environmental pollution.

[0007] Specifically, the present invention provides the following technical solutions:

[0008] A long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component, comprising a structural layer and a surface layer disposed on the structural layer;

[0009] The raw materials for preparing the structural layer include the following components by mass: 700-900 parts of white cement, 150-300 parts of white mineral admixture, 80-160 parts of white quartz powder, 90-130 parts of fiber, 900-1300 parts of white quartz sand, 5-20 parts of water reducer, 1-3 parts of defoamer, and 150-210 parts of water;

[0010] The raw materials for preparing the surface layer include the following components in parts by mass: 700-900 parts of white cement, 120-240 parts of white mineral admixture, 50-100 parts of white quartz powder, 900-1300 parts of white quartz sand, 5-20 parts of water reducer, 1-3 parts of defoamer, 150-210 parts of water, 10-60 parts of aqueous stearic acid emulsion, 30-70 parts of zeolite, and 40-100 parts of nano-TiO2.

[0011] In a long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component provided by the present invention, the structural layer contains fibers, which mainly meet the mechanical performance requirements of the component, and the surface layer is thin and does not contain fibers. The surface of the component is smooth and flat under the premise of meeting the mechanical performance requirements. By adding components such as aqueous stearic acid emulsion, nano-TiO2 and modified zeolite, the component has the functions of hydrophobic self-cleaning, photocatalytic degradation self-cleaning and anti-cracking.

[0012] Preferably, each of the white cements is of grade PW 52.5, with a whiteness of ≥89.

[0013] Preferably, each of the white mineral admixtures is independently one or both of white silica fume and white kaolin; the 28-day activity index of the white silica fume is ≥115%, and the 28-day activity index of the white kaolin is ≥105%.

[0014] Preferably, each of the white quartz powders has a particle size of 200 mesh and a SiO2 content greater than 97wt%.

[0015] Preferably, each of the white quartz sands is a mixture of 20-40 mesh white quartz sand and 40-80 mesh white quartz sand in a mass ratio of 6-8:2-4 (more preferably 7:3), and the SiO2 content is greater than 97%.

[0016] Preferably, the fiber is one or more of alkali-resistant glass fiber, polypropylene fiber (PP), polyvinyl alcohol fiber (PVA), polyoxymethylene fiber (POM), and steel fiber.

[0017] Preferably, each of the water reducing agents is a polycarboxylic acid water reducing agent with a water reducing rate of 35%-45%.

[0018] Preferably, each of the defoaming agents is a polyether-modified silicone defoaming agent.

[0019] Preferably, the content of stearic acid in the aqueous stearic acid emulsion is 30-35wt%.

[0020] Preferably, the particle size of the zeolite is 100-200 mesh, and the 28d activity index is ≥98%.

[0021] Preferably, the average particle size of the nano-TiO2 is 25-50nm.

[0022] The present invention also provides a method for preparing the above-mentioned long-lasting, stain-resistant, crack-resistant and high-strength UHPC decorative component, comprising the following steps:

[0023] S1: preparing alkali heat-treated modified zeolite: adding zeolite into an alkali solution and stirring for a period of time, washing, drying and calcining to obtain alkali heat-treated modified zeolite;

[0024] S2 Preparation of modified zeolite-TiO2: Add nano-TiO2 into water and stir for a period of time to obtain a suspension, then place it in a 60-70℃ water bath and stir for 4-6 hours to obtain TiO2 sol; add alkali-heat-treated modified zeolite into the TiO2 sol, stir for 1-2 hours, then dry and calcine to obtain modified zeolite-TiO2;

[0025] S3: preparing UHPC surface layer slurry: mixing white cement, white mineral admixture, quartz sand, quartz powder, aqueous stearic acid emulsion, water, modified zeolite-TiO2, water reducing agent and defoaming agent to form surface layer UHPC slurry;

[0026] S4 forming surface layer: spray or pour the surface layer UHPC slurry into the mold;

[0027] S5: preparing UHPC structural layer slurry: stirring and mixing white cement, white mineral admixture, quartz sand, quartz powder, fiber, water, water reducing agent and defoaming agent to form structural layer UHPC slurry;

[0028] S6 Forming structural layer: within 0.8-2 hours after the surface layer is formed, the structural layer UHPC slurry is sprayed or poured into the mold;

[0029] S7 Curing and Forming: After the structural layer is formed, it is covered with a layer of plastic film, demoulded after standard curing for 2-3 days, steam cured for 2-3 days, and finally standard cured for 5-7 days.

[0030] Preferably, the stirring speed in steps S1 and S2 is 50-100 rad / min.

[0031] Preferably, the temperature of the steam curing in step S7 is 70-90°C.

[0032] The beneficial effects of the present invention are at least:

[0033] 1) The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component provided by the present invention introduces a hydrophobic self-cleaning function into UHPC: silane compounds are currently common materials used to prepare hydrophobic concrete, but their disadvantages are that they are expensive and will greatly reduce the mechanical properties of concrete. For this reason, the present invention uses aqueous stearic acid emulsion as a hydrophobic additive, which is cheaper and has less impact on mechanical properties. Aqueous stearic acid emulsion is an aqueous emulsion that can be easily dispersed evenly during the stirring process of UHPC material. The contact angle (CA) between the surface of the obtained UHPC substrate and water droplets is greater than 150°, and the rolling angle (SA) is less than 10°, which has a good hydrophobic self-cleaning effect. At the same time, because it is added to the surface UHPC material, the hydrophobic self-cleaning effect can accompany the entire service life of UHPC, and has a long-lasting self-cleaning ability;

[0034] 2) The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component provided by the present invention introduces a photocatalytic degradation self-cleaning function in UHPC: Nano-TiO2 has photocatalytic properties and can use ultraviolet rays in sunlight to decompose organic matter, such as pollutants, bacteria, molds, and algae, so as to keep the concrete surface clean. This self-cleaning effect helps to reduce the maintenance and cleaning costs of the concrete surface. The photocatalytic properties of nano-TiO2 can also help reduce pollutants in the air, such as nitrogen dioxide (NOx) and volatile organic compounds (VOCs), which has a positive impact on improving the air quality of the surrounding environment. However, due to the low specific surface area and poor stability of cement-based materials, the photocatalytic degradation efficiency is low. The surface of zeolite is relatively rough and has abundant pores. This structure helps TiO2 particles to be evenly dispersed at the nano level, providing more active sites to participate in the photocatalytic reaction, thereby improving the photocatalytic efficiency. To this end, the present invention uses alkali heat treatment to modify zeolite to make it have a higher specific surface area and porosity, so as to increase its loading and binding degree for nano-TiO2, which can help the conduction of light and the diffusion of pollutants while dispersing and fixing nano-TiO2. A strong chemical bond is generated between nano-TiO2 and zeolite. After multiple cycle experiments, the sample still maintains a high catalytic degradation efficiency and has long-term stable degradation performance;

[0035] 3) The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative components provided by the present invention improve the strength, crack resistance and durability of UHPC: the surface of zeolite is relatively rough and has abundant pores. This porous characteristic is more obvious after modification. It absorbs water in UHPC and then slowly releases water, thereby having an internal curing effect and reducing the self-shrinkage of UHPC. At the same time, the water absorption and release process of zeolite promotes the optimization of the interface transition zone and the further densification of the later hardened slurry, thereby improving the later strength of UHPC. Because the UHPC decorative components of the present invention have excellent long-term stain resistance and crack resistance, the durability is better than that of conventional UHP C decorative components, and it has the advantages of longer service life and lower maintenance costs;

[0036] 4) The long-lasting stain-resistant and crack-resistant high-strength UHPC decorative component provided by the present invention adopts a double-layer structure of a structural layer and a surface layer. The structural layer contains fibers and has good mechanical properties. The surface layer has long-lasting stain resistance, crack resistance, self-cleaning and other functionalities on the premise that the strength meets the requirements. In addition, since it is white, it is convenient to add dyes for color adjustment according to needs, and the decorative effect is good. In the construction process, since the coating, finishing and other processes are omitted, it meets the needs of low-carbon green development. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is described clearly and completely below. The following embodiments are used to illustrate the present invention, but are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in the field or the product instructions are used.

[0038] In the following examples, the white cement used was sourced from Albopolante (Anqing) Co., Ltd., using grade P.W52.5 with a whiteness of 89.5;

[0039] The white mineral admixture used is white silica fume, which comes from Luoyang Anke Building Materials Co., Ltd., and its 28d activity index is 116.3%;

[0040] The white quartz powder used is from Tianjin Liguo Weiye Trading Co., Ltd., with a particle size of 200 mesh and a SiO2 content greater than 97wt%.

[0041] The fiber used is alkali-resistant glass fiber, which comes from Taishan Glass Fiber Co., Ltd.;

[0042] The polycarboxylate water reducer used was from Shandong Xiufu New Material Technology Co., Ltd., with a water reduction rate of 35.9%;

[0043] The defoamer used was a polyether-modified silicone defoamer, sourced from Beijing Kenye Trading Co., Ltd.;

[0044] The content of stearic acid in the aqueous stearic acid emulsion used was 30 wt%, which was sourced from Shandong Xiufu New Materials Technology Co., Ltd.;

[0045] The zeolite used was from Gongyi Yuanheng Water Purification Material Factory, with a particle size of 100-200 mesh and a 28d activity index of 98.8%;

[0046] The nano-TiO2 used comes from Evonik Degussa, with an average particle size of 25nm.

[0047] Examples 1-3

[0048] A long-lasting, stain-resistant, crack-resistant and high-strength UHPC decorative component, comprising a structural layer and a surface layer, wherein the structural layer is made of the following raw materials: 800 parts by mass of PW 52.5 white silicate cement, 220 parts by mass of white silica fume, 100 parts by mass of white quartz powder, 110 parts by mass of alkali-resistant glass fiber, 750 parts by mass of 20-40 mesh white quartz sand, 350 parts by mass of 40-80 mesh white quartz sand, 17 parts by mass of polycarboxylate water reducer, 1.5 parts by mass of defoamer, and 190 parts by mass of water;

[0049] The raw material composition of the surface layer is shown in Table 1, wherein the white quartz sand is a mixture of 20-40 mesh white quartz sand and 40-80 mesh white quartz sand in a mass ratio of 15:7.

[0050] Table 1 Surface layer components of Examples 1-3 and Comparative Examples 1-2

[0051]

[0052]

[0053] The preparation method of modified zeolite-TiO2 in the surface material is as follows: immerse the zeolite in a NaOH solution with a concentration of 0.2mol / L, the mass ratio is 1:90, stir at 60rad / min for 5h, rinse with distilled water until the pH value is 7, place it in a 100℃ oven for drying, then place it in a 400℃ muffle furnace for calcination for 2h and take it out to obtain alkali heat-treated modified zeolite, cool it to room temperature for standby use. Add a certain amount of distilled water (the mass ratio of nano-TiO2 to distilled water is 1:10) to nano-TiO2 and stir it continuously to obtain a suspension, then place it in a 60-70℃ water bath and stir it for 5h to obtain TiO2 sol, add alkali heat-treated modified zeolite to the TiO2 sol, stir it for 1.5h and place it in a 100℃ oven for drying, then place it in a 400℃ muffle furnace for calcination for 2h and take it out, cool it to room temperature to obtain modified zeolite-TiO2.

[0054] The method for preparing the above-mentioned lightweight UHPC decorative component comprises the following steps:

[0055] (1) Preparing UHPC surface layer slurry: weighing white cement, white mineral admixture, quartz sand, quartz powder, aqueous stearic acid emulsion, water, modified zeolite-TiO2, water reducer and defoamer according to proportion, stirring and mixing evenly to form a surface layer UHPC slurry;

[0056] (2) Forming surface layer: pouring the surface layer slurry into the mold by pouring;

[0057] (3) Preparing UHPC structural layer slurry: weighing white cement, white mineral admixture, quartz sand, quartz powder, fiber, water, water reducing agent and defoaming agent in proportion and stirring and mixing them evenly to form a structural layer UHPC slurry;

[0058] (4) Forming the structural layer: within 0.8-2 hours after the surface layer is formed, the surface layer slurry is poured into the mold by pouring;

[0059] (5) Curing and molding: After molding, lamination is performed, standard curing is performed for 2 days, and then demolding is performed, steam curing is performed for 3 days, and then standard curing is performed for 7 days.

[0060] Furthermore, the stirring speed in steps S1 and S2 is 80 rad / min.

[0061] Furthermore, the steam curing process in step S7 is: heating for 2 hours - constant temperature for 32 hours - cooling for 2 hours; and the constant temperature is 80°C.

[0062] Test Method

[0063] (1) The compressive strength, flexural strength and tensile strength were tested in accordance with GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The results are shown in Table 2 below.

[0064] (2) Water absorption and frost resistance shall be carried out in accordance with the provisions of T / CBMF 172-2022 "Ultra-High Performance Concrete (UHPC) Decorative Products".

[0065] (3) Surface contact angle: Before the experiment, the sample surface must be cleaned with ethanol. The contact angle test uses a contact angle tester to measure the size of the contact angle between the horizontal UHPC material surface and the water droplets. Three sample surfaces are taken from each group, and each surface is measured three times, and the average of these nine values ​​is taken.

[0066] Table 2 Performance test data of Examples 1-3 and Comparative Examples 1-2

[0067]

[0068] According to the data in Table 2, it can be seen from the comparison of Examples 1-3 and Comparative Example 2 that after adding aqueous stearic acid emulsion and modified zeolite-TiO2, the mechanical properties (compressive strength, flexural strength, tensile strength) of UHPC are further improved, and the addition of aqueous stearic acid emulsion can greatly reduce the water absorption rate and improve the frost resistance. At the same time, the surface contact angle is greater than 150° and the rolling angle is less than 10°, and it has super hydrophobic ability; it can be seen from Comparative Example 1 and Comparative Example 2 that the addition of modified zeolite-TiO2 can effectively reduce the water absorption rate, greatly improve the frost resistance of UHPC, and thus improve the durability; it can be seen from Comparative Example 1 and Example 1 that the addition of aqueous stearic acid emulsion can greatly reduce the water absorption rate, increase the surface contact angle, reduce the rolling angle, and improve the frost resistance.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component, characterized in that: It comprises a structural layer and a surface layer disposed on the structural layer; The raw materials for preparing the structural layer include the following components by mass: 700-900 parts of white cement, 150-300 parts of white mineral admixture, 80-160 parts of white quartz powder, 90-130 parts of fiber, 900-1300 parts of white quartz sand, 5-20 parts of water reducer, 1-3 parts of defoamer, and 150-210 parts of water; The raw materials for preparing the surface layer include the following components in parts by mass: 700-900 parts of white cement, 120-240 parts of white mineral admixture, 50-100 parts of white quartz powder, 900-1300 parts of white quartz sand, 5-20 parts of water reducer, 1-3 parts of defoamer, 150-210 parts of water, 10-60 parts of aqueous stearic acid emulsion, 30-70 parts of zeolite, and 40-100 parts of nano-TiO2.

2. The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component according to claim 1 is characterized in that: Each of the white cements is of PW 52.5 grade with a whiteness of ≥89.

3. The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component according to claim 1 or 2, characterized in that: Each of the white mineral admixtures is independently one or both of white silica fume and white kaolin; the 28-day activity index of the white silica fume is ≥115%, and the 28-day activity index of the white kaolin is ≥105%.

4. The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component according to claim 1 or 2, characterized in that: The particle size of each of the white quartz powders is 200 meshes, and the SiO2 content is greater than 97wt%.

5. The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component according to claim 1 or 2, characterized in that: Each of the white quartz sands is mixed with 20-40 mesh white quartz sand and 40-80 mesh white quartz sand in a mass ratio of 6-8:2-4, and the SiO2 content is greater than 97%.

6. The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component according to claim 1 or 2, characterized in that: The fiber is one or more of alkali-resistant glass fiber, polypropylene fiber, polyvinyl alcohol fiber, polyoxymethylene fiber, and steel fiber.

7. The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component according to claim 1 or 2, characterized in that: Each of the water reducing agents is a polycarboxylic acid water reducing agent with a water reducing rate of 35%-45%; And / or, each of the defoamers is a polyether-modified silicone defoamer; And / or, the content of stearic acid in the aqueous stearic acid emulsion is 30-35wt%.

8. The long-lasting, stain-resistant, crack-resistant, high-strength UHPC decorative component according to claim 1 or 2, characterized in that: The particle size of the zeolite is 100-200 mesh, and the 28d activity index is ≥98%; And / or, the average particle size of the nano-TiO2 is 25-50nm.

9. The method for preparing the long-lasting, stain-resistant, crack-resistant and high-strength UHPC decorative component according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: preparing alkali heat-treated modified zeolite: adding zeolite into an alkali solution and stirring for a period of time, washing, drying and calcining to obtain alkali heat-treated modified zeolite; S2 Preparation of modified zeolite-TiO2: Add nano-TiO2 into water and stir for a period of time to obtain a suspension, then place it in a 60-70℃ water bath and stir for 4-6 hours to obtain TiO2 sol; add alkali-heat-treated modified zeolite into the TiO2 sol, stir for 1-2 hours, then dry and calcine to obtain modified zeolite-TiO2; S3: preparing UHPC surface layer slurry: mixing white cement, white mineral admixture, quartz sand, quartz powder, aqueous stearic acid emulsion, water, modified zeolite-TiO2, water reducing agent and defoaming agent to form surface layer UHPC slurry; S4 forming surface layer: spray or pour the surface layer UHPC slurry into the mold; S5: preparing UHPC structural layer slurry: stirring and mixing white cement, white mineral admixture, quartz sand, quartz powder, fiber, water, water reducing agent and defoaming agent to form structural layer UHPC slurry; S6 Forming structural layer: within 0.8-2 hours after the surface layer is formed, the structural layer UHPC slurry is sprayed or poured into the mold; S7 curing and molding: After the structural layer is formed, it is coated, standard curing is carried out for 2-3 days, then demoulding is carried out, steam curing is carried out for 2-3 days, and finally standard curing is carried out for 5-7 days.

Citation Information

Patent Citations

  • Self-luminous self-cleaning high-crack-resistance UHPC (Ultra High Performance Concrete) curtain wall plate surface protection material and preparation method thereof

    CN117430386A

  • Organosilicon waterproof agent for ultra-high performance concrete plate and preparation method of organosilicon waterproof agent

    CN117844370A

  • Self-clean self-purification cement-based facing material and production method thereof

    CN102838330A

  • Saltpetering-resistant, stain-resistant and self-cleaning decorative cement-based product and preparation method thereof

    CN114853398A

  • UHPC decorative plate

    CN115073088A